A preliminary analysis of microplastics in edible versus non-edible tissues from seafood samples. (August 2020) - Akoueson, Fleurine; Sheldon, Lisa M.; Danopoulos, Evangelos; Morris, Steve; Hotten, Jessica; Chapman, Emma; Li, Jiana; Rotchell, Jeanette M.
Abstract: Plastics have been widely reported to be present in the environment yet there are still many questions regarding the extent of this and the impacts these may have on both the environment and human health. The purpose of this investigation is to determine levels of micro and mesoplastic (MP), in the 1–5000 μm range, in commercially important species of finfish and shellfish. Additionally, to determine and compare the relative MP levels in edible versus non-edible tissues, and consider the wider implications in terms of human health concerns with a preliminary risk identification approach. For several fish species, samples taken from typically non-edible (gills, digestive system) and edible (muscle) flesh, and were analysed separately. Scallops, where all tissues are edible, were analysed whole. Significant differences were observed in the number of particles isolated from the finfish gills and digestive tissues relative to the control samples, but not in the edible flesh. For scallops, the abundance of particles in the Scottish samples did not vary significantly from the control, while the Patagonian scallops displayed significantly higher numbers of MPs. Characterisation of MPs by FTIR microscopy found that 16–60% (depending on species) were polyethylene terephthalate (PET) and polyethylene (PE) in origin. The risk identification results validate MPs as an emerging risk in the food chain and establish seafood as a vector for the exposure and uptake of MPs through the ingestion route for humans. Levels of MPs in seafood, and a direct link to the human food chain, suggests that their quantification be included as one food safety measure. Graphical abstract: Image 1 Highlights: Fish gill and gut tissue contain higher levels of particles relative to control samples. Fish flesh contains numbers of particles similar to background control levels. Particle levels in scallops were higher than fish tissues and species dependent. Of the microplastics characterized, PET and PE, were the most commonly detected.